2016
DOI: 10.1093/neuonc/now155
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival in AIDS-related primary central nervous system lymphoma

Abstract: Background. The optimal therapeutic approach for patients with AIDS-related primary central nervous system lymphoma (AR-PCNSL) remains undefined. While its incidence declined substantially with combination antiretroviral therapy (cART), AR-PCNSL remains a highly aggressive neoplasm for which whole brain radiotherapy (WBRT) is considered a standard first-line intervention. Methods. To identify therapy-related factors associated with favorable survival, we first retrospectively analyzed outcomes of AR-PCNSL pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 43 publications
0
22
0
7
Order By: Relevance
“…34,35 Dose-adjusted etoposide, prednisone, vincristine, cyclophosphamide, and doxorubicin (EPOCH), an infusional regimen given over 5 days, emerged as Table 1. OS of HIV lymphoma subtypes both pre-and post-ART Pre-ART, % Current ART era, % Burkitt lymphoma 10-40 36,57,58,119 70-80 61,62 DLBCL 40 119 70-80 36,37 HL 55 87 80-90 86,87 PBL 6 64 75 68 Primary CNS lymphoma 20 69 60 73,74 the predominant approach after a 2003 US National Cancer Institute (NCI) study showed a 79% complete remission (CR) rate. 36 Building on EPOCH, AMC trial AMC-034 favored the addition of concurrent over sequential rituximab, the anti-CD20 antibody 37 ; the study found a 12% rate of febrile neutropenia, a 28% rate of any grade 3 or 4 infection, and 2-year rates of progression-free survival (PFS) and overall survival (OS) in the range of 70%.…”
Section: Subtypes Of Hiv-associated Nhlmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 Dose-adjusted etoposide, prednisone, vincristine, cyclophosphamide, and doxorubicin (EPOCH), an infusional regimen given over 5 days, emerged as Table 1. OS of HIV lymphoma subtypes both pre-and post-ART Pre-ART, % Current ART era, % Burkitt lymphoma 10-40 36,57,58,119 70-80 61,62 DLBCL 40 119 70-80 36,37 HL 55 87 80-90 86,87 PBL 6 64 75 68 Primary CNS lymphoma 20 69 60 73,74 the predominant approach after a 2003 US National Cancer Institute (NCI) study showed a 79% complete remission (CR) rate. 36 Building on EPOCH, AMC trial AMC-034 favored the addition of concurrent over sequential rituximab, the anti-CD20 antibody 37 ; the study found a 12% rate of febrile neutropenia, a 28% rate of any grade 3 or 4 infection, and 2-year rates of progression-free survival (PFS) and overall survival (OS) in the range of 70%.…”
Section: Subtypes Of Hiv-associated Nhlmentioning
confidence: 99%
“…71 A pilot study using only zidovudine (1.5 g twice daily), ganciclovir (5 mg/kg twice daily), and IL-2 (2 000 000 U twice daily) had 2 of 5 patients remaining in CR at 28 months and 52 months, but closed early because of low patient accrual. 72 Induction regimens are generally based on high-dose methotrexate, and retrospective studies of AIDSrelated primary CNS lymphoma include 14 ART-era patients whose 5-year OS was 60%, 73 and 51 ART-era patients whose 5year OS was 48%. 74 Several novel approaches are available for HIV 2 primary CNS NHL, but there are no data on their effectiveness in the setting of HIV.…”
Section: Primary Cns Lymphomamentioning
confidence: 99%
“…Epstein-Barr virus (EBV) is detected in virtually all cases of AIDS-related PCNSL, distinct from PCNSL arising in the immunocompetent, in which 5% to 15% of cases are EBV positive. 7 …”
Section: Diagnosis Pathogenesis and Radiographic Assessmentmentioning
confidence: 99%
“…In our study, all patients had a history of HT. Lymphoma was a malignant tumour originating from the lymphatic haematopoietic system leading to the enlargement of cervical lymph nodes [41].…”
Section: Discussionmentioning
confidence: 99%